Investigation of Sr-substituted Ba1-xSrx(Zn1/3Nb2/3)O3 complex perovskites: structural, electrical and electrochemical properties - Feng, Y.; Tan, K.B.; Chang, S.K.; Sulaiman, Y.; Lim, H.N.; Lu, M.; Wang, Y. (Elsevier, 2024)
Herein we report the structural, dielectric and electrochemical properties of Ba1-xSrx(Zn1/3Nb2/3)O3 (BSZN, 0 ≤ x ≤ 1) solid solution synthesised by solid-state reaction. A complete substitutional solid solution was obtained, wherein the BSZN cubic perovskites of the space group of Pm 3‾ m were obtained at x ≤ 0.6 while the pseudo-cubic phases were discernible at x > 0.6. The nano-sized crystallites, as determined by both Scherrer and Williamson-Hall analyses, supported the claim of large polyhedral grains of 0.1–0.3 μm by FE-SEM. Both ε′ and tan δ were found to vary consistently with increasing dopant concentration, except for an anomalous observation for the composition, x = 0.6 with the lowest tan δ of 0.0783 and the highest ε′ of 27.5. Such phenomenon could be attributed to the combined effects of larger grain size, higher relative density and stronger polarisation per molar volume. The impedance analysis revealed that these BSZN perovskites were of the negative temperature coefficient of resistance (NTCR) type. The combined plots of imaginary modulus (M″) and impedance (Z″) against frequency showed the short-range movement of localised charge carriers, suggesting a non-Debye-type relaxation process.